Computed tomography findings of complications resulting from cardiopulmonary resuscitation. (March 2015) - Kashiwagi, Yuta; Sasakawa, Tomoki; Tampo, Akihito; Kawata, Daisuke; Nishiura, Takeshi; Kokita, Naohiro; Iwasaki, Hiroshi; Fujita, Satoshi
Abstract: Introduction: This retrospective study was conducted to evaluate injuries related to cardiopulmonary resuscitation (CPR) and their associated factors using postmortem computed tomography (PMCT) and whole body CT after successful resuscitation. Methods: The inclusion criteria were adult, non-traumatic, out-of-hospital cardiac arrest patients who were transported to our emergency room between April 1, 2008 and March 31, 2013. Following CPR, PMCT was performed in patients who died without return of spontaneous circulation (ROSC). Similarly, CT scans were performed in patients who were successfully resuscitated within 72 h after ROSC. The injuries associated with CPR were analysed retrospectively on CT images. Results: During the study period, 309 patients who suffered out-of hospital cardiac arrest were transported to our emergency room and received CPR; 223 were enrolled in the study. The CT images showed that 156 patients (70.0%) had rib fractures, and 18 patients (8.1%) had sternal fractures. Rib fractures were associated with older age (78.0 years vs. 66.0 years, p  < 0.01), longer duration of CPR (41 min vs. 33 min, p  < 0.01), and lower rate of ROSC (26.3% vs. 55.3%, p  < 0.01). All sternal fractures occurred with rib fractures and were associated with a greater number of rib fractures, higher age, and a lower rate of ROSC than rib fractures only cases. Bilateral pneumothorax was observed in two patients with rib fractures. Conclusions: PMCT is useful for evaluating complications related to chest compression. Further investigations with PMCT are needed to reduce complications and improve the quality of CPR.